Clinical validation of fall prevention behavior in a hospital environment - Jéssica Naiara de Medeiros Araújo; Ana Paula Nunes de Lima Fernandes; Amanda Barbosa da Silva; Laísla Alves Moura; Marcos Antonio Ferreira Júnior; Allyne Fortes Vitor
ABSTRACT Objective: Clinically validate the Nursing Outcome Behavior of falls prevention in hospitalized patients. Method: This was a cross-sectional study developed at a public university hospital with a sample of 45 patients. The data collection was performed through the evaluation of four nurses, with a double used the instrument with the constitutive and operational definitions of the indicators and magnitudes of the Fall Prevention Behavior Result, while the other pair did not use such definitions. Results: When applying the non-parametric analysis of variance by the Friedman test, ten indicators showed statistical differences between the inferences made by the evaluators for each patient. In relation to the intraclass correlation coefficient, confidence interval and p value assigned to each indicator of the scale, most of the indicators were statistically significant. Conclusions: The instrument referring to the Fall Behavior Outcome Behavior was considered valid for the study population.